Study of Learning Implementation Sports Physical Education and Health in Lumajang Health Vocational High School - Arif Budi Raharjo; Gigih Siantoro; Dwi Cahyo Khartiko; Khurotul Aini (JUARA : Jurnal Olahraga, 2021)
This research aims to study how the learning planning and implementation of Physical Education, Sports, and Health learning can be used as evaluation material to improve Physical Education, Sports, and Health learning in schools. This research is action research with qualitative and quantitative descriptive methods using models from Kemmis and Mc. Taggart consists of one cycle or a round of activities which include: -1) Planning (plan), (2) Action (action), (3) Observation (observing), (4) Reflection (reflecting), and planning revision will be carried out cycle. Data processing is done by reducing data, presenting data, and making conclusions. The study results indicate that the planning and implementation aspects of academic supervision improve performance in developing learning devices and on the implementation aspects. From the results of the study, there were the findings of teacher performance not following the action in the field, such as the brakes that still copied paste from fellow teachers, the facilities were inadequate and had sports outside the school because the school was still new and did not have sports facilities, the clock of the faded subjects in SMK only 2 hours of lessons run out on a trip from school to the sport. The conclusion in this study is that after being done through the filling of teacher performance appraisal instruments given to physical education teachers, it can be obtained from cycle I to cycle II the results of better teacher educators after being given assistance and supervision.